Analysis of The Cycling Trend During the Pandemic of COVID 19 Towards Small and Medium Enterprises (UMKM) Income - Ramdani, Irham (International Journal of Social Science and Business, 2020)
The Corona pandemic has take down the vital parts of the economic sector. The implementation of the Large Scale Social Restriction (PSBB) has forced people to stay at home. Meanwhile, they also obliged to maintain their well being and health to prevent themselves infected by the Corona Virus Disease (COVID 19). On of the many ways to prevent the virus attack is by doing exercises, most of the society choose cycling as their exercise during the pandemic. This condition leads to the increase of the demands of bicycle and its spare parts although their prices is also increasing. This phenomena could increase the income of the Small and Medium Enterprises. The aim of this research is to analyze the impact of cycling trend during the pandemic of COVID 19 towards the income of small-medium enterprise, specifically the ones in the domain of bicycle. This research will use the qualitative descriptive approach. The interview data will be collected and categorized based on the source of the information, and will be presented in narrative voice showing the increase of small and medium bicycle enterprises’s income, so we can conclude that there is an impact of the cycling trend during the pandemic of COVID 19 towards the increase of the small medium bicycle enterprise, whether it is online, offline, the selling of bicycle, the spare parts, or the accessories.